2022
DOI: 10.31083/j.jin2101006
|View full text |Cite
|
Sign up to set email alerts
|

The effect of insulin receptor deletion in neuropeptide Y neurons on hippocampal dependent cognitive function in aging mice

Abstract: Insulin is known to act in the central nervous system to regulate several physiological and behavioural outcomes, including energy balance, glucose homeostasis and cognitive functioning. However, the neuronal populations through which insulin enhances cognitive performance remain unidentified. Insulin receptors are found in neuropeptide-Y (NPY) expressing neurons, which are abundant in the hypothalamus and hippocampus; regions involved in feeding behaviour and spatial memory, respectively. Here we show that mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 55 publications
(70 reference statements)
2
7
0
Order By: Relevance
“…There was no effect of genotype on blood glucose (including AUC values) and plasma insulin levels following peripheral glucose injection. These results could be considered surprising due to the conditional IR knockout, however, the current data aligns with previous GTT results using this IR lox/lox ;NPY Cre/+ mouse model ( Goodman et al, 2022 ). To specify, knocking out IRs on NPY neurons does not elicit any obvious effects on peripheral insulin sensitivity and glucose tolerance.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…There was no effect of genotype on blood glucose (including AUC values) and plasma insulin levels following peripheral glucose injection. These results could be considered surprising due to the conditional IR knockout, however, the current data aligns with previous GTT results using this IR lox/lox ;NPY Cre/+ mouse model ( Goodman et al, 2022 ). To specify, knocking out IRs on NPY neurons does not elicit any obvious effects on peripheral insulin sensitivity and glucose tolerance.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, despite expression of NPY within other regions of the brain, such as the hypothalamus, the deficits observed in the current study appear to be predominately mediated by NPY-located hippocampal neurons. This is supported by immunohistochemical validation experiments from a recent publication of ours, which demonstrated that insulin signaling within the dentate gyrus of the hippocampus is significantly downregulated in IR lox/lox ;NPY Cre/+ mice ( Goodman et al, 2022 ). Although these results do suggest that insulin signaling on NPY neurons plays a key role in spatial memory, they do not rule out the possibility that additional neuronal subtypes are involved in potentiating hippocampal cognitive functioning.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…In the current issue, Goodman et al [10] report investigations of a role for IR signaling in NPY neurons of the hippocampus in the context of cognitive functioning. The authors used a mouse model of cell-specific knockout for IR in NPY-expressing neurons using Cre-LoxP technology.…”
mentioning
confidence: 99%